2018
DOI: 10.1016/j.geoforum.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The production of human-wildlife conflict: A political animal geography of encounter

Abstract: This study examines how transformations of a regional rural economy have produced new geographies of encounter between agricultural communities, their livestock, and carnivores surrounding Bandipur National Park in Karnataka, India. We analyze state discourses of human-wildlife conflict alongside the perspectives of rural agricultural communities about changes in human-wildlife interactions. Our study shows how state narratives about human-wildlife conflict mask more foundational changes in the livelihood stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 94 publications
0
82
0
5
Order By: Relevance
“…In Slovenia, however, the key factor in predicting the attitude towards bears was the perception of how harmful the bears are [25], not their real damage and its regional differences. It is possible that differences in LC acceptance are of economic background-related to the GDP of the countries [1] or changes in the rural economy [15].…”
Section: Country-related Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Slovenia, however, the key factor in predicting the attitude towards bears was the perception of how harmful the bears are [25], not their real damage and its regional differences. It is possible that differences in LC acceptance are of economic background-related to the GDP of the countries [1] or changes in the rural economy [15].…”
Section: Country-related Differencesmentioning
confidence: 99%
“…Acceptance of damage-causing species by local people is usually related to multiple factors, including psychological ones [10,11]. For instance, shifts in landscape structure due to agriculture [12,13] and land abandonment, as well as changes in societies and culture may affect the equilibrium of human-carnivore cohabitation [14,15]. It has been shown that teenagers' acceptance might be more crucial than the adult acceptance for the future of wildlife conservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolves remain targets of political ire and violence throughout the West, as perhaps the quintessential instance of human-wildlife conflict. Bringing insights from critical environmental history and cultural landscape studies together with more recent work in more-than-human geographies can complicate ideas of restoration as always partial, always political claims to (and productions of) space (Cronon, 1992(Cronon, , 1995Whatmore, 2002;Margulies and Karanth, 2018). We might better understand both wolf conflict and broader tensions of multiple use through the metaphor of landscape as palimpsest (Meinig, 1979, 6), in which historical patterns and claims are layered but never fully erased.…”
Section: Contested Belonging and The Wolf Questionmentioning
confidence: 99%
“…Human-primate interactions are influenced by diverse cultural, social, ecological, and other components that may be unique to geographical regions and are fundamental to the continued existence of remaining primate populations (Dore 2017;Hill and Webber 2010;Lee and Priston 2005;Parathian et al 2018;Waters et al 2018a). Many negative human-primate interactions are underpinned by social or political conflicts where, for example, marginalized people consider wildlife to be the state's responsibility and hold it responsible for the losses they incur to their livelihoods (Anand et al 2018;Margulies and Karanth 2018). This perception is particularly common among people living around protected areas or where the state excludes local people from forest or wildlife management.…”
Section: Introductionmentioning
confidence: 99%